Legal Effectiveness of Protecting Those, Who Have a Mortgage Denominated in Swiss Francs, in the Context of Limitation Periods - Nadolska, Aleksandra (Journal of Finance and Financial Law, 2020)
In Poland, there was no uniform court jurisprudence regarding the rationales and grounds for can-celing the loan agreement, as well as the recognition of only certain contractual terms as unfair, consequently – also as to the application of limitation periods for the reimbursement of claims paid on the basis of abusive clause or invalid legal action. The situation was not changed by the EU Court of Justice judgment dated on the 3rd of October 2019 (C-260/18 Dziubak vs. Raiffeisen). Meanwhile, it is desirable and necessary for national courts to start settling mortgage denominated in Swiss francs cases in the spirit of EU regulations, because it was within them that the idea of full legal protection of the consumer was adopted, in principle according to which the implementation of a claim for restitution cannot be dependent on the limitation period. The purpose of the article is to answer the question: Does the restitution effect include – apart from the previous legal status – the restoration of the financial condition of contractors? Answer-ing this question is necessary to determine whether judicial recognition of the terms of contract as unfair can be limited as to the type of the effect. The above was the basis for the formulation of the following research thesis: determination of unfairness of contractual conditions in court proceedings will always have the character and ex tunc effect towards property and non-property rights, regardless of whether the decision in this matter is constitutive or declaratory. The presented matter determined the layout and content of the article, in which the issue of limi-tation periods (included in the preliminary rulings and the EU Court of Justice judgement) was dis-cussed in many aspects, the division of judgments into constitutive and declarative ones, as well as the essence and function of substantive limitation periods were explained.